Fostering Job Satisfaction: Uncovering the Impact of Work Environment and Compensation at Kolaka Transportation Office - Jusniati Jusniati; Hendrik Hendrik; Hanif Kurniadi (International Forum of Researchers and Lecturers, 2023)
The primary objectives of this study are twofold: (1) To assess the influence of the work environment on the job satisfaction of non-state civil servants, and (2) To investigate the impact of compensation on job satisfaction among non-state civil apparatus employees. This research adopts a quantitative approach, involving data collection methods such as observation, documentation, and the distribution of surveys. The research encompasses the entire population of non-state civil apparatus employees at the Kolaka Transportation Service, with a sample size of 135 individuals selected through a census technique, enabling a comprehensive examination of the population. The analysis of data encompassed an assessment of the measurement model and an investigation of the structural model through the application of Smart PLS 4.0. The research findings reveal a positive and statistically significant correlation between the work environment and compensation variables and the job satisfaction of non-state civil servant employees.